Abnormal Magnetic Resonance Image Signature in Virologically Stable HIV Individuals. (25th October 2022) - Strain, Jeremy F; Cooley, Sarah A; Tomov, Dimitre; Boerwinkle, Anna; Ances, Beau M
Abstract: Background: With implementation of combination antiretroviral therapy (cART), changes to brain integrity in people with HIV (PWH) are subtle compared to those observed in the pre-cART era. T1-weighted/T2-weighted (T1w/T2w) ratio has been proposed as a measure of cortical myelin. This study examines T1w/T2w values between virologically controlled PWH and persons without HIV (PWoH). Methods: Virologically well-controlled PWH (n = 164) and PWoH (n = 120) were compared on global and regional T1w/T2w values. T1w/T2w values were associated with HIV disease variables (nadir and current CD4 T-cell count, and CNS penetration effectiveness of cART regimen) in PWH, and as a function of age for both PWoH and PWH. Results: PWH had reduced global and regional T1w/T2w values compared to PWoH in the posterior cingulate cortex, caudal anterior cingulate cortex, and insula. T1w/T2w values did not correlate with HIV variables except for a negative relationship with CNS penetration effectiveness. Greater cardiovascular disease risk and older age were associated with lower T1w/T2w values only for PWH. Conclusions: T1w/T2w values obtained from commonly acquired MRI protocols differentiates virologically well-controlled PWH from PWoH. Changes in T1w/T2w ratio do not correlate with typical HIV measures. Future studies are needed to determine the biological mechanisms underlying this measure. Abstract : The T1w/T2w signature, calculated from commonly acquired MRI scans and proposed as a marker of cortical myelin, is significantly reduced in virologically well-controlled people with HIV compared to HIV-negative individuals.